Novel management of diabetes in kidney transplantation. Issue 1 (January 2021) - Ong, Song C.; Rhee, Connie M.
Abstract : Purpose of review: Posttransplant diabetes mellitus (PTDM) is a prevalent complication in kidney transplant recipients, and has been associated with worse short-term and long-term outcomes. Recent findings: While hyperglycemia is frequently seen in the early posttransplant period because of surgical stress, infection, and use of high-dose steroids, the diagnosis of PTDM should be established after patients are clinically stable and on stable maintenance immunosuppression. In the early posttransplant period, hyperglycemia is typically treated with insulin, and pilot data have suggested potential benefit of lower vs. higher glycemic targets in this setting. Growing data indicate lifestyle modifications, including dietary interventions, physical activity, and mitigation of obesity, are associated with improved posttransplant outcomes. While there are limited data to support a first-line antidiabetic medication for PTDM, more established pharmacotherapies such as sulfonylureas, meglitinides, and dipetidyl peptidase IV inhibitors are commonly used. Given recent trials showing the benefits of sodium–glucose cotransporter 2 inhibitors and glucagon-like peptide 1 receptor agonists upon kidney outcomes in nontransplant patients, further study of these agents specifically in kidney transplant recipients are urgently needed. Summary: Increasing evidence supports a multidisciplinary approach, including lifestyle modification, obesity treatment, judicious immunosuppression selection, and careful utilization of novel antidiabetic therapies in PTDM patients.